Upholding a Code Not Their Own: Non-Muslim Minority Leadership in the Internalization of Islamic Organizational Culture - Rizkia, Fadila Nur; Setianti, Yanti; Nugraha, Aat Ruchiat (Jurnal Sains Sosio Humaniora, 2026)
Studies of Islamic work culture generally assume that religious values are best transmitted by leaders sharing the majority's faith. This ethnographic study questions this assumption by examining PT X, a sharia-oriented startup where a Christian Chief Operating Officer (COO) models and enforces Manhaj Salaf principles. Using NVivo-assisted analysis integrating Hymes, Philipsen, and Schein, we investigate how this minority leader communicates and internalizes a majority-religion code. Findings reveal that to navigate a tense environment marked by collective employee silence and harsh CEO directives, the COO employs a protective communication strategy. He acts as a structural "brake pedal," softening top-down messages and migrating reprimands to private channels to preserve employees' communal social faces. Crucially, the COO internalizes the Islamic code through deliberate functional reasoning such as reframing prayer as focus renewal rather than dogmatic compliance. This functionally driven internalization expands Philipsen’s fourth proposition: identity difference forecloses automatic meaning-making, compelling deeper, deliberative engagement with a speech code. Ultimately, cross-faith value internalization depends on functional alignment and consistent leadership behavior, rather than solely on shared religious identity.